Electrical conductivity and electrical modulus properties of 13SrO-5.5Fe2O3-O.5Al2O3-8B2O3 magnetic glass ceramic - Yakuphanoğlu, Fahrettin; Zaitsev, D. D.; Trusov, L. A.; Kazin, P. E. (Elsevier, 2007)
The direct and alternating current conductivity and electrical modulus properties of 13SrO-5.5Fe(2)O(3)-0.5Al(2)O(3)-8B(2)O(3) magnetic glass ceramic have been investigated by complex impedance spectroscopy and direct current conductivity techniques. The direct current conductivity results indicate that 13SrO-5.5Fe(2)O3-0.5Al(2)O(3)-8B(2)O(3) magnetic glass ceramic exhibits an oxide semiconductor behavior with activation energy (Delta E = 0.37 eV) and conductivity at room temperature (sigma(25) = 2.97 x 10(-8)S/cm) values and a thermally activated process conductivity mechanism. Alternating conductivity results suggest that the correlated barrier hopping conductivity is dominant in alternating current conductivity mechanism of the sample. The dielectric constant values of SrO-Al2O3-Fe2O3-B2O3 magnetic glass ceramic increase with increasing temperature. The imaginary part of the modulus at different temperatures shows a relaxation peak and its position shifts to higher frequency with increasing temperature. This suggests a temperature-dependent relaxation. The activation energy of the relaxation process and relaxation time at infinite temperature were found to be 0.26 eV and 3.29 x 10(-8) s, respectively. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: oxide; magnetic semiconductor; electrical conductivity; glass ceramics; strontium hexaferrite